AB0856 Evaluation of Cardiac Capacity Parameters in Patients with Juvenile Idiopathic Arthritis. (15th July 2016) - Acer, S.; Karaahmet, O.Z.; Bal, A.; Başaran, Ö.; Cakci, A.
Abstract : Background: Children with juvenile idiopathic arthritis (JIA) are believed to have a lower cardiopulmonary capacity and functional ability. This means that they face more problems in performing daily activities compared with healthy children (1). Anaerobic capacity is important because most daily activities performed by children are anaerobic in nature (2). The association between anaerobic physical fitness and functional ability emphasized the importance of anaerobic physical fitness in children with JIA (3). Objectives: The purpose of this study is to examine whether children with JIA have lower cardiac capacity compared to healthy children and determine the clinical features that might be related to low aerobic capacity in children with JIA. Methods: 32 JIA patients and 11 healthy children aged between 6–16 years old participated in this study. The age, sex, height, weight, body mass index, disease duration, disease subtype, and medications of the participants were noted. Disease activity, functional disability and quality of life were measured with Disease Activity Score-28, Childhood Health Assessment Questionnaire and Pediatric Quality of Life scores, respectively. Knee or hip involvement in the patients was detected with physical examination. The ergospirometry stress test with bicycle was applied to all the participants to determine their cardiac capacity. The participants began the test with a load of half of their weight and a speed of 100 rpm (rapid per minute) and continued with a load that increased by 1 watt per 3 minutes. They were asked to pass the anaerobic threshold (respiratory exchange ratio). The VO2peak (the maximum volume of the oxygen consumed per minute) values were recorded to assess the aerobic capacity. The time passed after the thresholds (anaerobic capacity) and the total test time were also recorded to measure the whole (aerobic and anaerobic) cardiac capacity. Results: The averages of the cardiac capacity parameters (VO2peak level for the aerobic capacity and the total test time for the cardiac capacity) of the JIA group were significantly lower than those of the control group (p=0.00, p=0.00). There was no significant difference between the JIA (5.88 ±4.13 min) and the control groups (10.50±5.40 min) in terms of the time passed after the threshold (p=0.15). The investigations of the parameters that affect the VO2peak level revealed that women had a lower VO2peak level (p=0.02) compared to men and the participants with knee or hip involvement had a lower VO2peak level (p=0.01) compared to the ones who had no such a sign. Sex and CHAQ were identified as the most determinant factors on VO2peak level when the other probable risk factors were corrected (p=0.00, p=0.04). Conclusions: This study shows that JIA patients have lower aerobic capacities. In JIA treatment, the lower limb involvement, physical functional state, and sex should be considered when targeting to increase the cardiopulmonary capacity of the patients In addition, customized treatment programs should be designed for the JIA patients. References: Houghton K. Physical activity, physical fitness, and exercise therapy in children with juvenile idiopathic arthritis. Phys Sportsmed 2012;40:77–82. van Brussel M. Lelieveld OT. van der Net J. Engelbert RH. Helders PJ. Takken T. Aerobic and anaerobic exercise capacity in children with juvenile idiopathic arthritis. Arthritis Rheum 2007;57:891–7. Disclosure of Interest: None declared